Altered Intracerebellar Functional Connectivity in Friedreich’s Ataxia: A Graph-Theory Functional MRI Study - Mario Tranfa; Teresa Costabile; Giuseppe Pontillo; Alessandra Scaravilli; Chiara Pane; Arturo Brunetti; Francesco Saccà; Sirio Cocozza (The Cerebellum, 2025)
Historically, Friedreich’s Ataxia (FRDA) has been linked to a relatively preserved cerebellar cortex. Recent advances in neuroimaging have revealed altered cerebello-cerebral functional connectivity (FC), but the extent of intra-cerebellar FC changes and their impact on cognition remains unclear. This study investigates intra-cerebellar FC alterations and their cognitive implications in FRDA. In this cross-sectional, single-center study, resting-state functional MRI data from 17 patients with FRDA (average age 27.7 ± 13.6 years; F/M = 6/11) and 20 healthy controls (HC) (average age 29.4 ± 9.7 years; F/M = 9/11), all of whom underwent neuropsychological testing, were analyzed. From functional connectivity matrices, graph measures were computed at both the network and node levels using two complementary parcellations. FRDA patients exhibited decreased global efficiency ( p = 0.04), nodal degree ( p = 0.001) and betweenness centrality ( p = 0.04) in the vermal portion of lobule VIII, along with reduced global efficiency in cerebellar regions belonging to the Control-A network ( p = 0.02), one of the three subdivisions of the Frontoparietal network. Verbal memory deficits correlated with global efficiency in both the vermal portion of lobule VIII ( r = 0.53, p = 0.02) and the cerebellar regions of the Control-A network ( r = 0.49, p = 0.05). Graph analysis revealed regional intra-cerebellar FC changes in FRDA, marked by reduced functional centrality in cerebellar regions of the vermis and responsible for executive functions. These changes correlated with cognitive alterations, highlighting the role of the cerebellar cortex in the cognitive impairment observed in FRDA.

CHARON: An Imaging-Based Diagnostic Algorithm to Navigate Through the Sea of Hereditary Degenerative Ataxias - Alessandra Scaravilli; Mario Tranfa; Giuseppe Pontillo; Bernard Brais; Giovanna De Michele; Roberta La Piana; Francesco Saccà; Filippo Maria Santorelli; Matthis Synofzik; Arturo Brunetti; Sirio Cocozza (The Cerebellum, 2024)
The complexity in diagnosing hereditary degenerative ataxias lies not only in their rarity, but also in the variety of different genetic conditions that can determine sometimes similar and overlapping clinical findings. In this light, Magnetic Resonance Imaging (MRI) plays a key role in the evaluation of these conditions, being a fundamental diagnostic tool needed not only to exclude other causes determining the observed clinical phenotype, but also to proper guide to an adequate genetic testing. Here, we propose an MRI-based diagnostic algorithm named CHARON (Characterization of Hereditary Ataxias Relying On Neuroimaging), to help in disentangling among the numerous, and apparently very similar, hereditary degenerative ataxias. Being conceived from a neuroradiological standpoint, it is based primarily on an accurate evaluation of the observed MRI findings, with the first and most important being the pattern of cerebellar atrophy. Along with the evaluation of the presence, or absence, of additional signal changes and/or supratentorial involvement, CHARON allows for the identification of a small groups of ataxias sharing similar imaging features. The integration of additional MRI findings, demographic, clinical and laboratory data allow then for the identification of typical, and in some cases pathognomonic, phenotypes of hereditary ataxias.

A Review of Brain and Pituitary Gland MRI Findings in Patients with Ataxia and Hypogonadism - Alessandra Scaravilli; Mario Tranfa; Giuseppe Pontillo; Bernard Brais; Giovanna De Michele; Roberta La Piana; Francesco Saccà; Filippo Maria Santorelli; Matthis Synofzik; Arturo Brunetti; Sirio Cocozza (The Cerebellum, 2023)

Ataxia and Hypogonadism: a Review of the Associated Genes and Syndromes - Giovanna De Michele; Luigi Maione; Sirio Cocozza; Mario Tranfa; Chiara Pane; Daniele Galatolo; Anna De Rosa; Giuseppe De Michele; Francesco Saccà; Alessandro Filla (The Cerebellum, 2023)